Trichohyalin gene expression is negatively correlated with the severity of dermatitis in a canine atopic dermatitis model - Marsella, Rosanna; Ahrens, Kim; Wilkes, Rachel; Munguia, Nathalie (Frontiers in Veterinary Science, 2024)
Introduction -Canine atopic dermatitis (AD) closely mimics human AD and is recognized as a beneficial animal model. House dust mites (HDM) are a common allergen for both species. The effects of chronic exposure to HDM on the skin have not been studied in a model and it is not known how changes in gene expression correlate to severity of dermatitis.Methods -We used an established canine model of AD and took biopsies before HDM exposure and 5 times during repeated allergen challenges (Days 1, 2, 8, 15 and 29). Severity of dermatitis was scored the same days.Results -Trichohyalin gene expression decreased the most (15-fold decrease on D29 vs D0) and negatively correlated with severity of dermatitis. Gap-junction protein gene expression increased over 3-fold on D1, D8 and D29 and positively correlated with severity of dermatitis. Compared to D0, IL-31 gene expression significantly increased on D8 (p=0.0098), D15 (p=0.0068) and D29 (p=0.0187) but correlation with severity of dermatitis did not reach significance.Discussion -This is the first report on trichohyalin, a protein belonging to S100 family, and gapjunction protein gene expression in the context of clinical severity of AD. We propose these proteins should be further investigated to better understand their role in this complex disease.